A DUE DILIGENCE STANDARD OF ATTRIBUTION IN CYBERSPACE. Issue 3 (8th March 2018) - Chircop, Luke
Abstract: The technical and legal challenges of attribution in cyberspace prevent the meaningful operation of the international law framework of State responsibility. Despite the anticipation surrounding its publication, the Tallinn Manual 2.0 went no further than its predecessor in offering a cogent legal solution to this problem. Instead, the Manual confined its analysis of attribution to the well-known provisions of the International Law Commission's Articles on State Responsibility. This article departs from the Tallinn Manual 2.0 in arguing that the due diligence principle offers a preferable and appropriate standard of attribution in cyberspace.